Odpowiedzi

2009-11-12T07:17:04+01:00
(x+3)(x-3)+y-x+2=(x-2)²+y
-2x+y=2

x²-9+y-x+2=x²-4+y
-2x+y=2

-9+y-x+2=-4+y
-2x+y=2

-7+y-x=-4+y
-2x+y=2

-x=3 /:(-1)
-2x+y=2

x=3
-2*3+y=2

x=3
-6+y=2

x=3
y=8

2009-11-12T11:08:12+01:00
(x+3)*(x-3)+y-x+2=(x-2)²+y
-2x+y=2
(x²-9)+y-x+2=x²-4x+4+y
-2x+y=2
x²-9+y-x+2-x²+4x-4-y=0
-2x+y=2
3x-2=0
-2x+y=2
3x=2
-2x+y=2
x=2/3
-2*2/3+y=2
-4/3+y=2
y=2+4/3
y=6/3+4/3
y=10/3

odp
x=2/3
y=10/3
2009-11-12T13:04:19+01:00
(x+3)(x-3)+y-x+2=(x-2)²+y
-2x+y=2

X²-9+y-x+2=x²-4x+4
y=2-2x

x²-x+2-2x-7=x²-4x+4
y=2-2x

x²-x²-3x+4x=7+4
y=2-2x

x=11
y=2-2×11

x=11
y=-20